Editorial: Role of the SUMOylation in cancer regulation - Chen, Xu; Smaldone, Giovanni; Piccaluga, Pier Paolo; Qi, Yitao (Frontiers in Molecular Biosciences, 2023)
In this special issue “Role of the SUMOylation in Cancer Regulation” there is a collection of original comprehensive research and reviews that describe the role of SUMOylation in cancer regulation (Table 1). SUMOylation is a post-translational modification process that involves the covalent conjugation of SUMO proteins to specific target proteins(Chang and Yeh, 2020). This process is critical in regulating various essential cellular processes, such as gene expression(Rodriguez-Castaneda et al., 2018;Ryu and Hochstrasser, 2021), DNA damage repair(Bergink and Jentsch, 2009;Cremona et al., 2012;Sarangi and Zhao, 2015;Garvin and Morris, 2017), and protein homeostasis(Da Silva-Ferrada et al., 2016). Dysregulation of SUMOylation has been linked to the pathogenesis and progression of various types of cancer, underscoring its significance in cancer biology(Chang and Yeh, 2020;Chen et al., 2021;Qin et al., 2021). Therefore, the SUMOylation pathway has gained increasing attention as a potential regulatory switch and a promising therapeutic target for cancer treatment. Given the critical regulatory role of SUMOylation in cancer biology and the latest research development in the field, we organized this topic to provide a comprehensive summary of the new mechanisms of SUMOylation in the regulation of tumor development (Figure 1). The following is the summary of the original research and reviews from each contributor for this special issue of “Role of the SUMOylation in Cancer Regulation”.